Heat-sealable laminated film

JP7643176B2Active Publication Date: 2025-03-11TOYOBO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021086269
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-21
Publication Date
2025-03-11
Estimated Expiration
2041-05-21

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、特定のバイオマス由来の原料から重合されたポリアミド樹脂をポリアミド6にブレンドした二軸延伸ポリアミドフィルムにバイオマス由来の原料を用いたポリエチレンをポリプロピレンに配合したシーラントフィルムを積層することで、耐熱性、耐衝撃性、耐屈曲ピンホール性に優れるとともに、カーボンニュートラルなヒートシール性積層フィルムが得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643176000001
    Figure 0007643176000001
  • Figure 0007643176000002
    Figure 0007643176000002
  • Figure 0007643176000003
    Figure 0007643176000003
Patent Text Reader

Abstract

To provide a carbon-neutral heat-sealable laminated film made of a biomass-derived raw material, with excellent heat resistance, impact resistance, and bending pinhole resistance.SOLUTION: There is provided a heat-sealable laminated film having a base layer and a sealant layer, in which the base material layer is a biaxially stretched polyamide film, and the biaxially stretched polyamide film contains 70 to 99 mass% of polyamide 6 and 1 to 30 mass% of polyamide whose raw material is at least partly derived from biomass as a polyamide resin, and the sealant layer is an unstretched polyolefin film, and the unstretched polyolefin film contains 70 to 95 mass% of a polypropylene resin and 5 to 30 mass% of a linear low-density polypropylene resin whose raw material is at least partly derived from biomass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-sealable laminate film that is suitable for use as a packaging film or the like. [Background technology]

[0002] Biaxially oriented films made of aliphatic polyamides, such as polyamide 6, have excellent impact resistance and pinhole resistance due to bending, and are widely used as various packaging materials.

[0003] In recent years, in order to build a recycling-oriented society, the use of biomass instead of fossil fuels has been attracting attention in the field of materials. Biomass is an organic compound that is photosynthesized from carbon dioxide and water, and by using it, it becomes carbon dioxide and water again, making it a so-called carbon-neutral raw material (the amount of carbon dioxide emitted and absorbed in the environment is the same, so the increase in carbon dioxide, a greenhouse gas, can be suppressed). The practical application of biomass plastics made from these biomass raw materials has been rapidly progressing, and biaxially oriented polyamide films made from biomass-derived raw materials have also been proposed (see, for example, Patent Document 1).

[0004] When used as a packaging material, the biaxially oriented polyamide film is laminated with a sealant film or the like to form a laminated film, which is then processed into a packaging bag, etc. As the sealant film, an unstretched linear low-density polyethylene film, an unstretched polypropylene film, etc. are used, but from the viewpoint of carbon neutrality, a sealant film containing polyethylene polymerized using a biomass-derived raw material has been proposed (for example, see Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2020 / 170714 [Patent Document 2] JP 2018-001612 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a heat-sealable laminated film which is excellent in heat resistance, impact resistance and pinhole resistance due to bending, and which is carbon-neutral and uses raw materials derived from biomass. [Means for solving the problem]

[0007] The present invention comprises the following configurations. [1] A heat-sealable laminate film having at least a base layer and a sealant layer, the base layer is a biaxially oriented polyamide film, the biaxially oriented polyamide film contains, as polyamide resins, 70 to 99 mass% of polyamide 6 and 1 to 30 mass% of polyamide at least a part of which is derived from biomass; The sealant layer is an unstretched polyolefin film, and the unstretched polyolefin film is a film containing 70 to 95 mass % of a polypropylene resin and a linear low-density polyolefin, at least a part of which is derived from biomass. ethylene Contains 5-30% by mass of resin. fruit, the sealant layer comprises a seal layer, a core layer and a laminate layer; The resin composition constituting the seal layer contains 94 to 100% by mass of a propylene-α-olefin random copolymer and 0 to 3% by mass of a linear low-density polyethylene, The resin composition constituting the core layer contains 25 to 97% by mass of a propylene-α-olefin random copolymer and 3 to 40% by mass of a linear low-density polyethylene, The resin composition constituting the laminate layer contains 25 to 70 mass% of a propylene-α-olefin random copolymer and 3 to 50 mass% of a linear low-density polyethylene, In the sealant layer, a laminate layer, a core layer, and a seal layer are present in this order from the surface in contact with the base layer. Heat sealable laminated film. [2] The heat-sealable laminate film according to [1], wherein the content of carbon-14 in the base layer is 1 to 30% based on the total carbon in the base layer. [3] The heat-sealable laminate film according to [1] or [2], wherein the polyamide at least a part of which is derived from a biomass-derived raw material in the base layer is at least one polyamide selected from the group consisting of polyamide 11, polyamide 410, polyamide 610, and polyamide 1010. [4] The heat-sealable laminate film according to any one of [1] to [3], wherein the content of carbon-14 in the sealant layer is 3 to 30% based on the total carbon in the sealant layer. 〔5〕 The carbon-14 content in the laminated film is 2 to 30% of the total carbon in the laminated film, [1] to 〔4〕 13. The heat-sealable laminate film according to claim 12. 〔6〕 (1)~ 〔5〕 A package using the heat-sealable laminate film according to any one of claims 1 to 4. Effect of the Invention

[0008] According to the present invention, by laminating a biaxially oriented polyamide film in which a polyamide resin polymerized from a specific biomass-derived raw material is blended with polyamide 6, and a sealant film in which polyethylene made from biomass-derived raw materials is blended with polypropylene, a heat-sealable laminated film that is excellent in heat resistance, impact resistance, and bending pinhole resistance as well as being carbon-neutral can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Base material layer] The substrate layer of the present invention is a biaxially stretched polyamide film. The biaxially stretched polyamide film contains, as polyamide resins, 70 to 99% by mass of polyamide 6 and 1 to 30% by mass of polyamide at least partly derived from biomass. By containing 70% by mass or more of polyamide 6, it is possible to obtain excellent mechanical strength such as impact strength and gas barrier properties such as oxygen, which are inherent to biaxially stretched polyamide films made of polyamide 6. In addition, by containing 1 to 30% by mass of polyamide at least partly derived from biomass, it is possible to obtain not only an effect of being less affected by the increase and decrease in carbon dioxide on the ground, but also improved bending pinhole resistance and abrasion pinhole resistance.

[0010] <Polyamide 6> The polyamide 6 used in the present invention is usually produced by ring-opening polymerization of ε-caprolactam. The polyamide 6 obtained by ring-opening polymerization is usually subjected to removal of lactam monomer with hot water, followed by drying and melt extrusion in an extruder.

[0011] The relative viscosity of polyamide 6 is preferably 1.8 to 4.5, and more preferably 2.6 to 3.2. If the relative viscosity is less than 1.8, the impact strength of the film is insufficient. If the relative viscosity is more than 4.5, the load on the extruder increases, making it difficult to obtain an unstretched film before stretching.

[0012] As polyamide 6, in addition to polyamide 6 polymerized from commonly used monomers derived from fossil fuels, polyamide 6 chemically recycled from waste polyamide 6 products such as waste plastic products, waste tire rubber, fibers, fishing nets, etc. As a method for obtaining chemically recycled polyamide 6 from waste polyamide 6 products, for example, a method can be used in which used polyamide products are collected, depolymerized to obtain ε-caprolactam, which is then purified and then polymerized into polyamide 6.

[0013] In addition, polyamide 6 that is mechanically recycled from waste materials generated during the polyamide film manufacturing process can be used in combination. Mechanically recycled polyamide 6 is a raw material that is made by recovering waste materials that are generated during the manufacturing of biaxially oriented polyamide film, such as non-standard, unshippable films and cut off pieces (edge ​​trims), and pelletizing them through melt extrusion or compression molding.

[0014] <Polyamide made at least partly from biomass-derived raw materials> Examples of polyamides used in the present invention, at least a part of which is derived from biomass, include polyamide 11, polyamide 410, polyamide 610, polyamide 1010, polyamide MXD10, and polyamide 11·6T copolymer resins.

[0015] Polyamide 11 is a polyamide resin having a structure in which monomers having 11 carbon atoms are bonded via amide bonds. Usually, polyamide 11 is obtained by using aminoundecanoic acid or undecane lactam as a monomer. In particular, aminoundecanoic acid is a monomer obtained from castor oil, and is therefore desirable from the viewpoint of carbon neutrality. The constituent units derived from these monomers having 11 carbon atoms preferably account for 50 mol% or more of all the constituent units in polyamide 11, more preferably 80 mol% or more, and may even be 100 mol%. Polyamide 11 is usually produced by ring-opening polymerization of the above-mentioned undecane lactam. Polyamide 11 obtained by ring-opening polymerization is usually subjected to removal of lactam monomer with hot water, dried, and then melt-extruded by an extruder. The relative viscosity of polyamide 11 is preferably 1.8 to 4.5, more preferably 2.4 to 3.2. If the relative viscosity is less than 1.8, the impact strength of the film is insufficient. If it is greater than 4.5, the load on the extruder increases, making it difficult to obtain an unstretched film before stretching.

[0016] Polyamide 410 is a polyamide resin having a structure in which a monomer having four carbon atoms is copolymerized with a diamine having ten carbon atoms. Usually, sebacic acid and tetramethylenediamine are used for polyamide 410. From an environmental perspective, it is preferable that the sebacic acid is made from castor oil, a vegetable oil. The sebacic acid used here is preferably made from castor oil from the viewpoint of environmental protection (especially from the viewpoint of carbon neutrality).

[0017] Polyamide 610 is a polyamide resin having a structure in which a diamine having 6 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, hexamethylenediamine and sebacic acid are used. Of these, sebacic acid is a monomer obtained from castor oil, and is therefore desirable from the viewpoint of carbon neutrality. The total of the constituent units derived from these monomers having 6 carbon atoms and the constituent units derived from monomers having 10 carbon atoms in PA610 is preferably 50 mol % or more, more preferably 80 mol % or more, and may be 100 mol % of all the constituent units.

[0018] Polyamide 1010 is a polyamide resin having a structure in which a diamine having 10 carbon atoms and a dicarboxylic acid having 10 carbon atoms are polymerized. Usually, 1,10-decanediamine (decamethylenediamine) and sebacic acid are used in polyamide 1010. Decamethylenediamine and sebacic acid are monomers obtained from castor oil, and are therefore desirable from the viewpoint of carbon neutrality. The total of the structural units derived from these diamines having 10 carbon atoms and the structural units derived from dicarboxylic acids having 10 carbon atoms in PA1010 is preferably 50 mol % or more, more preferably 80 mol % or more, and may be 100 mol % of all structural units.

[0019] In the base layer of the present invention, the lower limit of the content of the polyamide, at least a part of which is derived from biomass, is not particularly limited, but is preferably 1% by mass, more preferably 3% by mass or more. The upper limit of the content is 30% by mass, more preferably 20% by mass. If the content of the polyamide, at least a part of which is derived from biomass, exceeds 30% by mass, the molten film may become unstable when cast, making it difficult to obtain a homogeneous unstretched film.

[0020] <Subsidiary materials, additives> The biaxially oriented polyamide film of the base layer may contain various additives such as other thermoplastic resins, lubricants, heat stabilizers, antioxidants, antistatic agents, anti-fogging agents, ultraviolet absorbers, dyes, pigments, etc., as necessary.

[0021] <Other thermoplastic resins> The biaxially stretched polyamide film of the base layer may contain a thermoplastic resin in addition to the polyamide 6 and the polyamide resin whose raw material is at least partially derived from biomass, as long as the object of the present invention is not impaired. Examples of the polyamide resin include polyamide 12 resin, polyamide 66 resin, polyamide 6·12 copolymer resin, polyamide 6·66 copolymer resin, polyamide MXD6 resin, and other polyamide-based resins. If necessary, thermoplastic resins other than polyamide-based resins, such as polyester-based polymers such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate, and polyolefin-based polymers such as polyethylene and polypropylene, may be contained. If the raw material of these thermoplastic resins is derived from biomass, it is preferable because it does not affect the increase or decrease of carbon dioxide on the ground, thereby reducing the environmental load.

[0022] <Lubricant> In order to improve the slipperiness and make it easier to handle, the biaxially stretched polyamide film of the base layer preferably contains organic lubricants such as fine particles or fatty acid amides as lubricants. The fine particles can be appropriately selected from inorganic fine particles such as silica, kaolin, and zeolite, and polymeric organic fine particles such as acrylic and polystyrene. In terms of transparency and slipperiness, it is preferable to use silica fine particles. The average particle size of the fine particles is preferably 0.5 to 5.0 μm, and more preferably 1.0 to 3.0 μm. If the average particle size is less than 0.5 μm, a large amount of addition is required to obtain good slipperiness. On the other hand, if it exceeds 5.0 μm, the surface roughness of the film tends to become too large, resulting in a poor appearance.

[0023] When the silica fine particles are used, the pore volume of the silica is preferably in the range of 0.5 to 2.0 ml / g, more preferably 0.8 to 1.6 ml / g. If the pore volume is less than 0.5 ml / g, voids are likely to occur, resulting in poor transparency of the film, whereas if the pore volume exceeds 2.0 ml / g, the fine particles tend not to form surface protrusions.

[0024] The biaxially stretched polyamide film of the base layer may contain fatty acid amide and / or fatty acid bisamide for the purpose of improving slipperiness. Examples of fatty acid amide and / or fatty acid bisamide include erucic acid amide, stearic acid amide, ethylene bisstearic acid amide, ethylene bisbehenic acid amide, and ethylene bisoleic acid amide. The content of fatty acid amide and / or fatty acid bisamide is preferably 0.01 to 0.40% by mass, and more preferably 0.05 to 0.30% by mass. If the content of fatty acid amide and / or fatty acid bisamide is less than the above range, slipperiness tends to deteriorate. On the other hand, if it exceeds the above range, wettability tends to deteriorate.

[0025] Polyamide resins such as polyamide MXD6 resin, polyamide 12 resin, polyamide 66 resin, polyamide 6·12 copolymer resin, and polyamide 6·66 copolymer resin can be added to the biaxially oriented polyamide film of the base layer in order to improve the slip properties.

[0026] <Antioxidants> The biaxially stretched polyamide film of the substrate layer may contain an antioxidant. The antioxidant is preferably a phenol-based antioxidant. The phenol-based antioxidant is preferably a completely hindered phenol-based compound or a partially hindered phenol-based compound. Examples of the phenol-based antioxidant include tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane. By containing a phenol-based antioxidant, the film-forming operability of the biaxially stretched polyamide film is improved. In particular, when recycled films are used as raw materials, the resin is prone to thermal degradation, which tends to cause operational problems in film production and increase production costs. On the other hand, by adding an antioxidant, the thermal degradation of the resin is suppressed and operationality is improved.

[0027] [Biaxially oriented polyamide film] The thickness of the base material layer is not particularly limited, but when used as a packaging material, it is usually 100 μm or less, and a thickness of 5 to 50 μm is generally used, and a thickness of 8 to 30 μm is particularly used.

[0028] The biaxially stretched polyamide film of the base layer preferably has a heat shrinkage rate in the range of 0.6 to 3.0% in both the MD and TD directions at 160°C for 10 minutes, more preferably 0.6 to 2.5%. If the heat shrinkage rate exceeds 3.0%, curling or shrinkage may occur when heat is applied in the next process, such as lamination or printing. Furthermore, the lamination strength with the sealant film may be weakened. Although it is possible to make the heat shrinkage rate less than 0.6%, it may become mechanically fragile. Furthermore, this is not preferable because it deteriorates productivity.

[0029] The impact strength of the biaxially oriented polyamide film is preferably 0.7 J / 15 μm or more, and more preferably 0.9 J / 15 μm or more.

[0030] The haze value of the biaxially stretched polyamide film is preferably 10% or less, more preferably 7% or less, and even more preferably 5% or less. A small haze value means good transparency and gloss, so when used for packaging bags, beautiful printing can be achieved and the product value is increased. Since the haze value increases when fine particles are added to improve the slipperiness of the film, if the film has two or more layers, the haze value can be reduced by adding fine particles only to the surface layer.

[0031] The dynamic friction coefficient of the biaxially stretched polyamide film is preferably 1.0 or less, more preferably 0.7 or less, and even more preferably 0.5 or less. When the dynamic friction coefficient of the film is small, the film has good slipperiness and is easy to handle. When the dynamic friction coefficient of the film is too small, the film is too slippery and difficult to handle, so the dynamic friction coefficient of the biaxially stretched polyamide film of the present invention is preferably 0.15 or more.

[0032] Biaxially oriented polyamide film is radiocarbon compliant with ASTM D6866-18 14 It is preferable that the content of carbon derived from biomass (also called biomass ratio) measured by the measurement of carbon dioxide in the atmosphere is 1 to 30% of the total carbon in the polyamide film. 14 Since carbon dioxide is contained in the atmosphere at a constant rate (105.5pMC), plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, contain 14 The content is known to be about 105.5 pMC. In addition, C in fossil fuels is 14 It is also known that almost no carbon is contained in the film. Therefore, the C contained in the total carbon atoms in the film is 14 By measuring the ratio of carbon derived from biomass, the ratio of carbon derived from biomass can be calculated.

[0033] [How to make biaxially oriented polyamide film] The biaxially stretched polyamide film of the substrate layer can be produced by a known production method. A typical production example is described below.

[0034] First, the raw resin is melt-extruded using an extruder, extruded from a T-die into a film, cast onto a cooling roll and cooled to obtain an unstretched film. The melting temperature of the resin is preferably 220 to 350°C. If it is lower than the above, unmelted matter may be generated, and defects or other poor appearance may occur, while if it exceeds the above, deterioration of the resin may be observed, and molecular weight and appearance may be reduced. The die temperature is preferably 250 to 350°C.

[0035] The cooling roll temperature is preferably −30 to 80° C., more preferably 0 to 50° C. To obtain an unstretched film by casting the film-like molten material extruded from the T-die onto a rotating cooling drum and cooling it, for example, a method using an air knife or an electrostatic adhesion method in which a static charge is applied can be preferably used. The latter method is particularly preferably used.

[0036] It is also preferable to cool the surface of the cast unstretched film opposite the cooling roll. For example, it is preferable to use a method of contacting the surface of the unstretched film opposite the cooling roll with a cooling liquid in a tank, a method of applying a liquid that evaporates with a spray nozzle, a method of spraying a high-speed fluid, or the like. The unstretched film thus obtained is stretched in biaxial directions to obtain the biaxially stretched polyamide film of the present invention.

[0037] The stretching method may be either a simultaneous biaxial stretching method or a sequential biaxial stretching method. In either case, the stretching method in the MD direction may be a multi-stage stretching method such as one-stage stretching or two-stage stretching. As described later, multi-stage MD stretching such as two-stage stretching is preferred in terms of physical properties and uniformity of physical properties in the MD direction and TD direction (isotropy) rather than one-stage stretching. Roll stretching is preferred for stretching in the MD direction in the sequential biaxial stretching method.

[0038] The lower limit of the MD stretching temperature is preferably 50° C., more preferably 55° C., and even more preferably 60° C. If it is less than 50° C., the resin does not soften and stretching may be difficult. The upper limit of the MD stretching temperature is preferably 120° C., more preferably 115° C., and even more preferably 110° C. If it exceeds 120° C., the resin may become too soft and stable stretching may not be possible.

[0039] The lower limit of the stretching ratio in the MD direction (when stretching in multiple stages, the total stretching ratio multiplied by each stretching ratio) is preferably 2.2 times, more preferably 2.5 times, and even more preferably 2.8 times. If it is less than 2.2 times, the thickness precision in the MD direction decreases, and the crystallinity becomes too low, which may decrease the impact strength. The upper limit of the stretching ratio in the MD direction is preferably 5.0 times, more preferably 4.5 times, and most preferably 4.0 times. If it exceeds 5.0 times, the subsequent stretching may become difficult.

[0040] In addition, when the MD stretching is performed in multiple stages, the above-mentioned stretching is possible in each stretching, but the stretching ratios must be adjusted so that the product of all MD stretching ratios is 5.0 or less. For example, in the case of two-stage stretching, the first stage stretching is preferably 1.5 to 2.1 times, and the second stage stretching is preferably 1.5 to 1.8 times.

[0041] The film stretched in the MD direction is stretched in the TD direction using a tenter, heat-set, and relaxed (also called relaxation). The lower limit of the stretching temperature in the TD direction is preferably 50°C, more preferably 55°C, and even more preferably 60°C. If the temperature is less than 50°C, the resin does not soften and stretching may be difficult. The upper limit of the stretching temperature in the TD direction is preferably 190°C, more preferably 185°C, and even more preferably 180°C. If the temperature exceeds 190°C, crystallization may occur, making stretching difficult.

[0042] The lower limit of the stretch ratio in the TD direction (when stretching in multiple stages, the total stretch ratio multiplied by each stretch ratio) is preferably 2.8, more preferably 3.2, even more preferably 3.5, and particularly preferably 3.8. If it is less than 2.8, the thickness precision in the TD direction decreases, and the crystallinity becomes too low, resulting in a decrease in impact strength. The upper limit of the stretch ratio in the TD direction is preferably 5.5, more preferably 5.0, even more preferably 4.7, particularly preferably 4.5, and most preferably 4.3. If it exceeds 5.5, the productivity may decrease significantly.

[0043] The lower limit of the heat setting temperature is preferably 210°C, more preferably 212°C. If the heat setting temperature is too low, the heat shrinkage rate becomes too large, which deteriorates the appearance after lamination and tends to reduce the laminate strength. The upper limit of the heat setting temperature is preferably 220°C, more preferably 218°C. If the heat setting temperature is too high, the impact strength tends to decrease.

[0044] The heat setting time is preferably 0.5 to 20 seconds. More preferably, it is 1 to 15 seconds. The heat setting time can be set appropriately by taking into account the heat setting temperature and the wind speed in the heat setting zone. If the heat setting conditions are too weak, crystallization and orientation relaxation become insufficient, causing the above problems. If the heat setting conditions are too strong, the film toughness decreases.

[0045] Relaxation treatment after heat setting is effective in controlling the heat shrinkage rate. The temperature for relaxation treatment can be selected within the range from the heat setting temperature to the glass transition temperature (Tg) of the resin, but a heat setting temperature of -10°C to Tg + 10°C is preferable. If the relaxation temperature is too high, the shrinkage speed will be too fast, which is undesirable and may cause distortion. Conversely, if the relaxation temperature is too low, relaxation treatment will not occur and the material will simply slacken, the heat shrinkage rate will not decrease, and dimensional stability will deteriorate.

[0046] The lower limit of the relaxation rate in the relaxation treatment is preferably 0.5%, more preferably 1%. If it is less than 0.5%, the heat shrinkage rate may not be sufficiently reduced. The upper limit of the relaxation rate is preferably 20%, more preferably 15%, and even more preferably 10%. If it exceeds 20%, sagging may occur in the tenter, making production difficult.

[0047] Furthermore, the biaxially stretched polyamide film of the base layer can be subjected to heat treatment or humidity conditioning treatment to improve dimensional stability depending on the application. In addition, in order to improve the adhesion of the film surface, corona treatment, coating treatment, flame treatment, printing, deposition of metals, inorganic oxides, etc. can be performed. As the deposition film formed by deposition processing, aluminum deposition film, and deposition film of silicon oxide or aluminum oxide alone or a mixture are preferably used. Furthermore, by coating a protective layer on these deposition films, oxygen barrier properties can be improved.

[0048] [Sealant layer] The sealant layer is an unstretched polyolefin film. The unstretched polyolefin film is a film containing 70 to 95% by mass of a polypropylene resin and a linear low-density polyolefin, at least a part of which is derived from biomass. ethylene The resin content is 5 to 30% by mass.

[0049] The unstretched polyolefin film preferably has a laminated structure, and has a seal layer, a core layer, and a laminate layer in this order. The seal layer and the laminate layer are layers located on the surface side of the unstretched polyolefin film, and the core layer is located between them. The laminate layer is a layer suitable for bonding a biaxially oriented polyamide film, and in practice, it is preferable to laminate it with the biaxially oriented polyamide film via an adhesive resin. The seal layer is a layer suitable for producing a package by heat sealing. By adopting the above layer structure, it is possible to contain more linear low-density polyethylene resin derived from biomass while maintaining the properties of the unstretched polypropylene film, which is a sealant layer with excellent heat resistance.

[0050] <Sealing layer> In the present invention, the polypropylene resin composition constituting the seal layer contains a propylene-α-olefin random copolymer from the viewpoint of heat seal strength. The content of the propylene-α-olefin random copolymer in the polypropylene resin composition constituting the seal layer is preferably 94% by mass or more, more preferably 97% by mass or more, even more preferably 99% by mass or more, and particularly preferably 100% by mass. By making it 94% by mass or more, sufficient heat seal strength can be obtained.

[0051] In the present invention, the polypropylene-based resin composition constituting the seal layer can contain a propylene homopolymer in order to improve the slipperiness. The content of the propylene homopolymer is preferably 3% by mass or less, more preferably 2% by mass, even more preferably 1% by mass or less, and particularly preferably 0% by mass, in terms of heat seal strength. If the seal layer contains a large amount of a polyethylene-based resin such as linear low-density polyethylene, the heat seal strength may decrease due to poor compatibility with each other.

[0052] In the present invention, the polypropylene resin composition constituting the seal layer may contain linear low-density polyethylene from the viewpoint of improving pinhole resistance upon bending. The content of linear low-density polyethylene is preferably 3% by mass or less, more preferably 2% by mass, even more preferably 1% by mass or less, and particularly preferably 0% by mass, from the viewpoint of heat seal strength.

[0053] <Core layer> In the present invention, the polypropylene resin composition constituting the core layer contains a propylene-α-olefin random copolymer from the viewpoint of heat seal strength. The content of the propylene-α-olefin random copolymer is preferably 25% by mass or more, more preferably 40% by mass or more, even more preferably 60% by mass or more, particularly preferably 75% by mass or more, and particularly preferably 80% by mass or more from the viewpoint of heat seal strength. From the viewpoint of bending pinhole resistance, it is preferably 97% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less.

[0054] In the present invention, the polypropylene-based resin composition constituting the core layer can contain a propylene homopolymer from the viewpoint of improving heat resistance. The content of the propylene homopolymer is preferably 30% by mass or more, more preferably 40% by mass or more, from the viewpoint of heat resistance. However, from the viewpoint of heat seal strength and bag rupture resistance, it is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 10% by mass or less, and particularly preferably 0% by mass.

[0055] In the present invention, the polypropylene resin composition constituting the core layer may contain linear low-density polyethylene in order to improve pinhole resistance. The content of linear low-density polyethylene is preferably 3% by mass or more, more preferably 8% by mass or more, even more preferably 12% by mass or more, and particularly preferably 15% by mass or more in terms of pinhole resistance. In terms of heat resistance, the content is preferably 40% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less, and particularly preferably 25% by mass or less.

[0056] <Laminate layer> In the present invention, the polypropylene-based resin composition constituting the laminate layer contains a propylene-α-olefin random copolymer from the viewpoint of heat seal strength. The content of the propylene-α-olefin random copolymer is preferably 25% by mass or more, more preferably 40% by mass or more, even more preferably 60% by mass or more, and particularly preferably 80% by mass or more from the viewpoint of heat seal strength. From the viewpoint of bending pinhole resistance, it is preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, particularly preferably 75% by mass or less, and particularly preferably 70% by mass or less.

[0057] In the present invention, the polypropylene-based resin composition constituting the laminate layer may contain a propylene homopolymer in order to improve heat resistance. The content of the propylene homopolymer is preferably 30% by mass or more, more preferably 40% by mass or more, in terms of heat resistance. However, in terms of heat seal strength and bag rupture resistance, the content is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 10% by mass or less, and particularly preferably 0% by mass.

[0058] In the present invention, the polypropylene resin composition constituting the laminate layer may contain linear low-density polyethylene in order to improve pinhole resistance upon bending. The content of linear low-density polyethylene is preferably 3% by weight or more in terms of pinhole resistance upon bending, more preferably 8% by weight or more, even more preferably 15% by weight or more, particularly preferably 20% by weight or more, and most preferably 25% by weight or more. In terms of heat resistance and heat seal strength, the content is preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 30% by weight or less.

[0059] In the unstretched polyolefin film of the present invention, the difference in the content of linear low-density polyethylene in the polypropylene resin composition constituting the seal layer and the core layer is preferably 1 to 28% by mass, more preferably 1 to 23% by mass, even more preferably 1 to 18% by mass, and particularly preferably 1 to 15% by mass. By keeping the difference in content at 28% by mass or less, the interlayer strength at the interface between the seal layer and the core layer can be kept high, and high heat seal strength can be obtained.

[0060] In the unstretched polyolefin film of the present invention, the difference in the content of the linear low-density polyethylene in the polypropylene resin composition constituting the core layer and the laminate layer is preferably 1 to 28% by mass, more preferably 1 to 23% by mass, even more preferably 1 to 18% by mass, and particularly preferably 1 to 15% by mass. By keeping the difference in content at 28% by mass or less, it is possible to maintain high interlayer strength at the interface between the core layer and the laminate layer, and to obtain high heat seal strength.

[0061] In the unstretched polyolefin film of the present invention, the content of the linear low-density polyethylene in the polypropylene resin composition constituting the core layer is preferably greater than the content of the linear low-density polyethylene in the polypropylene resin composition constituting the seal layer, and the content of the linear low-density polyethylene in the polypropylene resin composition constituting the laminate layer is preferably greater than the content of the linear low-density polyethylene in the polypropylene resin composition constituting the core layer. This makes it easier for the linear low-density polyethylene in the film to be uniformly dispersed, which is advantageous in terms of bending pinhole resistance. In addition, a high ratio of polypropylene resin in the resin close to the heat seal surface can provide high heat seal strength.

[0062] By using a propylene-α-olefin random copolymer with a low melting point for the sealing layer and a propylene-α-olefin random copolymer with a high melting point for the layers and laminate layers, it is possible to improve heat seal strength while also improving heat resistance and pinhole resistance against bending.

[0063] <Propylene-α-olefin random copolymer> The propylene-α-olefin random copolymer in the present invention may be a copolymer of propylene and at least one α-olefin other than propylene having 2 or 4 to 20 carbon atoms. Examples of the α-olefin monomer having 2 or 4 to 20 carbon atoms include ethylene, butene-1, pentene-1, 4-methylpentene-1, hexene-1, and octene-1.

[0064] The propylene-α-olefin random copolymer is preferably made of ethylene from the viewpoint of heat sealability. At least one type may be used, and two or more types may be mixed and used as necessary. Particularly preferred is a propylene-ethylene-butene random copolymer in which the main monomer is propylene and a certain amount of ethylene and butene are copolymerized.

[0065] The lower limit of the melt flow rate (MFR) of the propylene-α-olefin random copolymer is preferably 0.6 g / 10 min, more preferably 1.0 g / 10 min, and even more preferably 1.2 g / 10 min. The uniformity of the film thickness may be impaired. The upper limit of the melt flow rate of the random copolymer is preferably 12.0 g / 10 min, more preferably 9.0 g / 10 min, and even more preferably 8.0 g / 10 min.

[0066] <Propylene homopolymer) The melt flow rate (MFR) of the propylene homopolymer (measured at 230°C under a load of 2.16 kg) is not particularly limited, but is preferably 1.0 g / 10 min to 10.0 g / 10 min, more preferably 2.0 g / min to 8.0 g / min. If it is less than 1 g / 10 min, the viscosity is too high and extrusion through a T-die is difficult, and if it exceeds 10 g / 10 min, problems such as stickiness of the film and poor impact strength (impact strength) of the film may occur. As the propylene homopolymer, isotactic polypropylene is preferred because it has high crystallinity and suppresses deterioration of the heat shrinkage rate.

[0067] <Linear low-density polyethylene> The linear low density polyethylene can be produced by a production method such as a high pressure method, a solution method, or a gas phase method. The linear low density polyethylene can be a copolymer of ethylene and at least one α-olefin having 3 or more carbon atoms. The α-olefin may be any of those generally called α-olefins, and is preferably an α-olefin having 3 to 12 carbon atoms, such as propylene, butene-1, hexene-1, octene-1, or 4-methyl-1-pentene. The copolymer of ethylene and α-olefin can be, for example, an ethylene-hexene-1 copolymer, an ethylene-butene-1 copolymer, or an ethylene-octene-1 copolymer, and from the viewpoint of bending pinhole resistance, an ethylene-hexene copolymer is preferred.

[0068] The linear low density polyethylene may include biomass-derived linear low density polyethylene, which is polymerized using ethylene derived from plants such as sugarcane and ethylene derived from fossil fuels such as petroleum or plants as part of the raw materials. From the viewpoint of carbon neutrality, biomass-derived linear low density polyethylene is said to have the effect of reducing carbon dioxide generation and to suppress global warming. When the biomass-derived linear low density polyethylene contains biomass-derived ethylene, the content is preferably 50% by mass or more, more preferably 80% by mass or more. When it is 50% or more, the carbon dioxide reduction effect is good. The upper limit is preferably 98%, more preferably 96%. Since it is preferable to copolymerize an α-olefin other than ethylene from the viewpoint of bending pinhole resistance, 98% by mass or less is preferable.

[0069] The lower limit of the MFR (measured at 190°C and 2.18 kg) of the linear low-density polyethylene is preferably 1.0 g / 10 min, more preferably 2.0 g / 10 min. The upper limit is preferably 7.0 g / min, more preferably 5.0. By keeping it within the above range, compatibility with polypropylene resins is good and high seal strength can be obtained.

[0070] The lower limit of the density of the linear low density polyethylene is preferably 910 kg / m 3 and more preferably 913 kg / m 3 910kg / m 3 By setting the thickness to 935 kg / m or more, good blocking resistance can be obtained. 3 and more preferably 930 kg / m 3 930kg / m 3 When the thickness is equal to or less than this, good resistance to bag rupture can be obtained.

[0071] <Additives> The unstretched polyolefin film may contain an appropriate amount of an antiblocking agent, an antioxidant, an antistatic agent, an antifogging agent, a neutralizing agent, a nucleating agent, a colorant, other additives, and an inorganic filler in any layer as necessary, within the scope of the object of the present invention.

[0072] The polyolefin resin composition constituting the unstretched polyolefin film may contain an antiblocking agent. Although one type of antiblocking agent may be used, the use of two or more types of inorganic particles with different particle sizes and shapes allows complex protrusions to be formed even on the unevenness of the film surface, and a higher level of blocking prevention effect can be obtained. The antiblocking agent to be added is not particularly limited, but inorganic particles such as spherical silica, amorphous silica, zeolite, talc, mica, alumina, hydrotalcite, and aluminum borate, and organic particles such as polymethyl methacrylate and ultra-high molecular weight polyethylene can be added.

[0073] The antiblocking agent contained in the polypropylene resin composition constituting the sealing layer is preferably 0.30% by mass or less, more preferably 0.25% by mass or less, based on the polyolefin resin of the layer to which it is added. By making it 0.30% by mass or less, it is possible to reduce the falling off of the antiblocking agent. In addition, it is preferably 0.05% by mass or more, more preferably 0.10% by mass or more. By making it 0.05% by mass or more, it is possible to obtain good antiblocking properties.

[0074] The antiblocking agent contained in the polypropylene resin composition constituting the laminate layer is preferably 0.30% by mass or less, more preferably 0.25% by mass or less, even more preferably 0.10% by mass or less, particularly preferably 0.05% by mass or less, and most preferably 0.05% by mass or less, based on the polyolefin resin of the layer to which it is added. By making the amount 0.30% by mass or less, it is possible to reduce the falling off of the antiblocking agent on the surface of the laminate layer.

[0075] The polyolefin resin composition constituting the unstretched polyolefin film may contain an organic lubricant. The inclusion of an organic lubricant improves the lubricity and anti-blocking effect of the film, improving the handling of the film. The reason for this is believed to be that the organic lubricant bleeds out and is present on the film surface, thereby exerting a lubricant effect and a mold release effect. The organic lubricant is preferably one having a melting point above room temperature. Examples of the organic lubricant include fatty acid amides and fatty acid esters. Specifically, oleic acid amide, erucic acid amide, behenic acid amide, ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, ethylene bisoleic acid amide, and the like. These may be used alone, but it is preferable to use two or more of them in combination, since it is possible to maintain the lubricity and anti-blocking effect even under harsh environments. The content of the organic lubricant in the polypropylene resin composition is preferably 0.15% by mass or less, and more preferably 0.10% by mass or less. By making it 0.15% by mass or less, blocking is unlikely to occur even when stored in a place exposed to high temperatures, such as a warehouse in summer. The content is preferably 0.02% by mass or more, and more preferably 0.025% by mass or more. By setting the content to 0.02% by mass or more, good slipperiness can be obtained.

[0076] The polyolefin resin composition constituting the unstretched polyolefin film may contain an antioxidant. Examples of the antioxidant include phenolic antioxidants, phosphite antioxidants, their combination, and those having phenolic and phosphite skeletons in one molecule. Examples of the neutralizing agent include calcium stearate.

[0077] [Unstretched polyolefin film] The lower limit of the thickness of the unstretched polyolefin film of the sealant layer is preferably 15 μm, more preferably 20 μm, and even more preferably 25 μm. If it is 15 μm or more, heat seal strength and bag break resistance are easily obtained. The upper limit of the film thickness is preferably 80 μm, more preferably 70 μm, even more preferably 60 μm, and particularly preferably 50 μm. If it is 80 μm or less, the film is not too stiff and is easy to process, and a suitable package is easily produced.

[0078] The haze value of the unstretched polyolefin film is preferably 20.0% or less. More preferably, it is 15.0%, and even more preferably, it is 10.0%. When it is 20.0% or less, visibility of the package is easily obtained. Linear low-density polyethylene has high crystallinity and is prone to increase in haze, but the increase in haze can be suppressed if it is added within the above-mentioned preferred range. The lower limit is preferably 1.0%, and more preferably 2.0%. When it is 1.0% or more, the unevenness of the film surface is not extremely small, so blocking of the inner surface of the package is unlikely to occur.

[0079] The static friction coefficient of the unstretched polyolefin film is preferably 0.70 or less, more preferably 0.50, and even more preferably 0.40. If it is 0.70 or less, the opposite surfaces slide easily when filling the package with food or when opening the package, and the opening is easy. The lower limit is preferably 0.10 or more, more preferably 0.20 or more, and particularly preferably 0.30. If it is 0.10 or more, the rolled film is less likely to collapse when transported.

[0080] The impact strength of the unstretched polyolefin film is preferably 0.20 J / 15 μm or more, more preferably 0.25 J, and even more preferably 0.30 J. By making it 0.20 J or more, the drop-breakage resistance of the package can be improved. An impact strength of 1.0 J is sufficient. The impact strength is largely dependent on the thickness and molecular orientation of the film. In addition, the impact strength and the drop-breakage resistance are not necessarily correlated.

[0081] The pin puncture strength of the unstretched polyolefin film is preferably 1.0 N or more, more preferably 1.5 N or more, and even more preferably 1.7 N or more. When it is 1.0 μm or more, the laminate has good pinhole resistance.

[0082] The plane orientation coefficient of the unstretched polyolefin film is preferably 0.000 or more, more preferably 0.001 or more. The upper limit of the plane orientation of the film is preferably 0.010 or less, more preferably 0.008 or less, and even more preferably 0.006 or less. If it is more than the above, the film may be stretched non-uniformly, and the thickness uniformity may be deteriorated.

[0083] The heat seal initiation temperature of the unstretched polyolefin film is preferably 110°C or higher, more preferably 120°C or higher. At 110°C or higher, the film has a high stiffness and is easy to handle. The upper limit of the heat seal initiation temperature is 150°C, more preferably 140°C, and even more preferably 130°C. At 150°C or lower, the package can be produced at high speed, which is economically advantageous. The heat seal initiation temperature is greatly affected by the melting point of the seal layer. Therefore, if linear low-density polyethylene is used for the core layer and the laminate layer, the change in the heat seal temperature can be suppressed.

[0084] The wet tension of the surface of the unstretched polyolefin film to be laminated with at least one film selected from the group consisting of polyamide resin film, polyester resin film, and polypropylene resin film is preferably 30 mN / m or more, more preferably 35 mN / m or more. If it is 30 mN / m or more, the laminate strength is unlikely to decrease. The upper limit of the wet tension is preferably 55 mN / m, more preferably 50 mN / m. If it is 55 mN / m or less, blocking between the films is unlikely to occur when the polyolefin resin film is wound on a roll.

[0085] The unstretched polyolefin film preferably contains 3 to 30% of biomass-derived carbon (also called biomass ratio) based on the total carbon in the unstretched polyolefin film, as determined by radiocarbon (C14) measurement according to ASTM D6866-18.

[0086] [Method of manufacturing unstretched polyolefin film] The method for producing the unstretched polyolefin film in the present invention can be, for example, an inflation method or a T-die method, but the T-die method is preferred in order to increase transparency. The inflation method uses air as a cooling medium, whereas the T-die method uses a cooling roll, making it an advantageous manufacturing method for increasing the cooling rate. By increasing the cooling rate, the crystallization of the unstretched sheet can be suppressed, which is advantageous in terms of transparency. For these reasons, the T-die method is preferred for producing a non-oriented sheet.

[0087] A typical manufacturing example is described below. The raw materials of the polypropylene resin composition for the seal layer, core layer, and laminate layer are mixed, melt-mixed and extruded in separate extruders, and the laminated sheet of the molten seal layer, core layer, and laminate layer is cast onto a cooling roll from a T-die to obtain a non-oriented sheet. The lower limit of the temperature of the cooling roll is preferably 15°C, more preferably 20°C. If it is less than the above, condensation may occur on the cooling roll, resulting in insufficient adhesion. The upper limit of the cooling roll is preferably 60°C, more preferably 50°C. If it exceeds the above, transparency may deteriorate.

[0088] [Heat-sealable laminated film] The heat-sealable laminated film of the present invention has a base layer and a sealant layer, but the laminated film can also be formed by interposing an adhesive layer, a printed layer, a metal layer, etc. between the base layer and the sealant layer. The lamination method can be a known method such as a dry lamination method or an extrusion lamination method, but any lamination method may be used. Specific examples are shown below.

[0089] Examples of layer configurations of the laminated film of the present invention: ONY / adhesive / CPP, ONY / adhesive / Al / adhesive / CPP, PET / adhesive / ONY / adhesive / CPP, PET / adhesive / ONY / adhesive / Al / adhesive / CPP, PET / adhesive / Al / adhesive / ONY / adhesive / CPP, ONY / adhesive / PET / adhesive / CPP, ONY / PE / CPP, ONY / adhesive / EVOH / adhesive / CPP, ONY / adhesive / aluminum-vapor-deposited PET / adhesive / CPP, CPP / adhesive / ONY / adhesive / LLDPE, ONY / adhesive / aluminum-vapor-deposited CPP. The abbreviations used in the above layer structure are as follows: / : represents the layer boundary ONY: Biaxially oriented polyamide film PET: Stretched polyethylene terephthalate film LLDPE: Unoriented linear low density polyethylene film CPP: Unstretched polypropylene film PE: Extrusion laminate or unstretched low density polyethylene film Al: Aluminum foil EVOH: Ethylene-vinyl alcohol copolymer resin Adhesive: An adhesive layer that bonds films together Aluminum vapor deposition: Indicates that aluminum is vapor-deposited.

[0090] [Characteristics of heat sealable laminated film] The bending resistance of the heat-sealable laminated film can be measured by pinhole evaluation. The number of pinholes after bending the heat-sealable laminated film 1000 times at 1° C. is preferably 20 or less, more preferably 15, and particularly preferably 10 or less. If the number is 20 or less, pinholes are unlikely to occur due to bending impact during transportation of the package.

[0091] The puncture strength of the heat-sealable laminate film is preferably 10 N or more, more preferably 12 N or more, and even more preferably 14 N or more. If it is 10 N or more, pinholes are unlikely to occur when the protrusions come into contact with a package.

[0092] The heat seal strength of the heat sealable laminated film is preferably 20N / 15mm or more, more preferably 25N / 15mm or more, and even more preferably 30N / 15mm or more. If it is 20N / 15mm or more, it is easy to obtain resistance to bag breakage. If the heat seal strength is 60N / 15mm, it is very excellent, and if it is 35N / 15mm, it is sufficient.

[0093] The heat-sealable laminate film preferably contains 2 to 30% of biomass-derived carbon (also called biomass degree) based on the total carbon in the heat-sealable laminate film, as determined by radiocarbon (C14) measurement according to ASTM D6866-18.

[0094] [Packaging] The heat-sealable laminate film of the present invention is processed into a package intended to protect the contents, such as foodstuffs, from dust, gas, and the like in the natural world. The package is produced by bonding the inner surfaces of the heat-sealable laminate film together using a heated heat seal bar or ultrasonic waves, and forming it into a bag shape. For example, two rectangular laminates are stacked with the sealant side facing inward, and processed into a four-sided sealed bag by heat sealing the four sides. The heat-sealable laminate film of the present invention can be processed into packages such as bottom-sealed bags, side-sealed bags, three-sided sealed bags, pillow bags, standing pouches, gusseted bags, and square-bottom bags.

[0095] The drop-break resistance of the package of the present invention is preferably 15 times or more, more preferably 20 times or more, and even more preferably 22 times or more. If it is 15 times or more, the package containing food is unlikely to break even when it is accidentally dropped. Drop-break resistance of about 30 times is sufficient. The drop-break resistance of the package is affected by the bending pinhole resistance, puncture strength, and heat seal strength of the laminate, and it is preferable that these properties are in the preferred range. EXAMPLES

[0096] The films were evaluated by the following measurement methods. Unless otherwise specified, the measurements were carried out in a measurement room with an environment of 23° C. and a relative humidity of 65%.

[0097] (1) Film thickness The obtained film was cut into 100 mm long pieces in the vertical direction, and conditioned for at least 2 hours in an environment with a temperature of 23°C and a relative humidity of 65%.Then, the thickness was measured using a thickness measuring device manufactured by Tester Sangyo at 10 equal positions in the width direction of the film (for narrow films, the positions were divided so that the width was sufficient to measure the thickness), and the average value was divided by the number of overlapping films to obtain the film thickness. The thickness of the A layer (base layer) was calculated based on the ratio of the resin discharge amounts of the A layer, the B layer, and the C layer.

[0098] (2) Haze value The haze value of the film was measured using a direct reading haze meter manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with JIS K7105.

[0099] (3) Biomass ratio The biomass content of the films was determined by radiocarbon (C14) measurement according to ASTM D6866-18 Method B (AMS).

[0100] (4) Heat shrinkage rate The heat shrinkage of the film was measured in each of the MD and TD directions by the following formula in accordance with the dimensional change test method described in JIS C2318, except that the test temperature was 160° C. and the heating time was 10 minutes. Heat shrinkage rate = [(length before treatment - length after treatment) / length before treatment] x 100 (%)

[0101] (5) Impact strength The impact strength of the film was measured using a film impact tester manufactured by Toyo Seiki Seisakusho, Ltd. The measured value was converted per 15 μm thickness and expressed as J (joule) / 15 μm.

[0102] (6) Degree of plane orientation The sample was taken from the center position in the width direction of the film. The refractive index (nx) in the longitudinal direction of the film and the refractive index (ny) in the width direction of the film were measured by an Abbe refractometer using sodium D line as a light source according to JIS K 7142-1996 A method, and the degree of planar orientation was calculated according to formula (1). Planar orientation degree (ΔP)=(nx+ny) / 2-nz (1)

[0103] (7)Piercing strength The puncture strength of the film was measured in accordance with "2. Test methods for strength, etc." in "Standards and Criteria for Foods, Additives, etc., Part 3: Apparatus and Containers and Packaging" (Ministry of Health and Welfare Notification No. 20, 1982) in the Food Sanitation Act. A needle with a tip diameter of 0.7 mm was pierced into the film at a piercing speed of 50 mm / min, and the strength at which the needle penetrated the film was measured, and this was taken as the puncture strength. The measurement was carried out at room temperature (23°C), and the puncture strength (unit: N) of the film obtained was divided by the actual thickness of the film to obtain the puncture strength (unit: N / μm).

[0104] (8) Wetting tension The wetting tension of the laminate layer surface was measured in accordance with JIS-K6768 Plastics-Films and Sheets-Wetting Tension Test Method.

[0105] (9) Heat seal initiation temperature The heat seal initiation temperature of the unstretched polyolefin film was measured in accordance with JIS Z 1713 (2009). At this time, the film was cut into a rectangular test piece (for heat sealing) of 50 mm x 250 mm (width direction x length direction of the film). The seal layer parts of two test pieces were overlapped, and a heat gradient tester (heat seal tester) manufactured by Toyo Seiki Seisakusho Co., Ltd. was used, with a heat seal pressure of 0.2 MPa and a heat seal time of 1.0 sec. Then, heat sealing was performed under conditions of increasing the temperature with a gradient of 5°C. After heat sealing, a test piece was cut out to a width of 15 mm. The test piece fused by heat sealing was opened at 180°, and the unsealed part was sandwiched in a zipper to peel off the sealed part. Then, the temperature at the time when the heat seal strength reached 4.9 N was obtained. The test machine used was a universal material testing machine 5965 manufactured by Instron Instruments Co., Ltd. The test speed was 200 mm / min. Measurements were performed with N=5, and the average value was calculated.

[0106] [Heat seal strength] Heat seal strength was measured in accordance with JIS Z1707. The specific procedure is as follows. Two heat sealable laminated films were used with a heat sealer to bond the seal layers of unstretched polyolefin films together. The heat seal conditions were upper bar temperature 120°C, lower bar 30°C, pressure 0.2MPa, and time 2 seconds. The adhesive sample was cut out to have a seal width of 15mm. Peel strength was measured at a tensile speed of 200mm / min using a tensile tester "AGS-KNX" (manufactured by Shimadzu Corporation). The peel strength is expressed as the strength per 15mm (N / 15mm).

[0107] (10) Pinhole resistance due to bending The heat-sealable laminated film was cut into a length of 280 mm and a width of 260 mm. The unstretched polyolefin film was made into a cylindrical shape of φ89 mm and height 260 mm so that the unstretched polyolefin film was on the inside, and fixed with cellophane tape. The sample was attached to a thermostatically-controlled Gelbo Flex Tester manufactured by Tester Sangyo Co., Ltd., and a bending load was applied 1000 times at 1°C. The sample was removed and the number of pinholes was measured. The unstretched polyolefin film was placed on a filter paper (Advantec, No. 50) with the side facing down, and the four corners were fixed with cellophane tape (registered trademark). Ink (Pilot ink (product number INK-350-Blue) diluted 5 times with pure water) was applied to the test film and spread over the entire surface using a rubber roller. After wiping off unnecessary ink, the test film was removed and the number of ink dots on the filter paper was counted. Measurements were performed with N=3, and the average value was calculated.

[0108] (11) Drop and tear resistance Using the heat-sealable laminated film, a four-sided sealed bag containing 200 ml of saturated saline was made with an inner dimension of 170 mm length and 120 mm width. The heat-sealing conditions were a pressure of 0.2 MPa for 1 second, a seal bar width of 10 mm, and a heat-sealing temperature of 160°C. The ends of the four-sided sealed bag were cut off, leaving a seal width of 5 mm. The bag was then left in a +5°C environment for 8 hours, after which the four-sided sealed bag was dropped from a height of 1.2 m onto a flat concrete floor so that the surface was horizontal. The bag was repeatedly dropped until it broke, and the number of repeated drops was counted. This was repeated for 20 samples, and the average value was calculated.

[0109] [Production Example 1] <Preparation of biaxially oriented polyamide film (ONY)> (ONY1) Using an apparatus consisting of an extruder and a 380 mm wide T-die, the following molten resin composition A was extruded from the T-die into a film, which was then cast onto a cooling roll whose temperature was controlled at 20°C and electrostatically adhered thereto to obtain an unstretched film having a thickness of 200 μm. Resin composition A: Polyamide 6 (manufactured by Toyobo Co., Ltd., relative viscosity 2.8, melting point 220°C) 97 parts by mass; Polyamide 11 (Arkema, relative viscosity 2.5, melting point 186°C) 3.0 parts by mass; 0.45 parts by mass of porous silica fine particles (manufactured by Fuji Silysia Chemical, average particle size 2.0 μm, pore volume 1.6 ml / g); and Fatty acid bisamide (ethylene bisstearic acid amide, manufactured by Kyoeisha Chemical Co., Ltd.) 0.15 parts by mass

[0110] The unstretched film obtained was introduced into a roll-type stretching machine, and by utilizing the difference in peripheral speed of the rolls, it was stretched 1.73 times in the MD direction at 80°C, and then further stretched 1.85 times at 70°C. Subsequently, this uniaxially stretched film was continuously introduced into a tenter-type stretching machine, preheated at 110°C, and then stretched 1.2 times in the TD direction at 120°C, 1.7 times at 130°C, and 2.0 times at 160°C, and then heat-set at 218°C, and then relaxed at 218°C by 7%, and then the surface on the side to be dry-laminated with a linear low-density polyethylene film was corona discharge-treated to obtain a biaxially stretched polyamide film. The evaluation results of the obtained biaxially stretched polyamide film are shown in Table 1.

[0111] (ONY2~ONY13) A biaxially stretched film was obtained in the same manner as ONY1, except that the raw material resin composition and film-forming conditions such as the heat setting temperature were changed as shown in Table 1. The evaluation results of the obtained biaxially stretched film are shown in Table 1. However, with ONY13, the molten resin could not be stably extruded from the T-die into a film shape, and a homogeneous unstretched film could not be obtained, so biaxial stretching was not possible.

[0112] The polyamide resins at least partially containing raw materials derived from biomass, namely polyamide 410, polyamide 610, and polyamide 1010, were as follows: Polyamide 410: (DSM, ECOPaXX Q150-E, melting point 250℃) Polyamide 610: (Arkema, RilsanS SMNO, melting point 222°C) Polyamide 1010: (Arkema, RilsanT TMNO, melting point 202°C)

[0113] [Table 1A]

[0114] [Table 1B]

[0115] [Table 1C]

[0116] [Production Example 2] <Preparation of unstretched polyolefin film (CPP)> (CPP1) The raw materials were adjusted based on the resin composition and ratio of each layer shown in Table 2. The adjustments in each layer shown in Table 2 were taken as 100 parts by weight, and 360 ppm of behenic acid amide was added as an organic lubricant to the sealing layer, and 2000 ppm of silica with an average particle size of 4 μm was added as an inorganic anti-blocking agent in a master batch. 2700 ppm of behenic acid amide was added as an organic lubricant to the core layer in a master batch.

[0117] (Materials used in the sealing layer) PP-1: Sumitomo Chemical Co., Ltd. Propylene-ethylene-butene random copolymer FL6745A (MFR 6.0g / 10min, melting point 130℃) LL-1: Braskem ethylene-hexene copolymer (plant-derived linear low-density polyethylene) SLH218 (MFR 2.3 g / min, density 916 kg / m3, melting point 126°C) Silica particles: Amorphous silica KMP130-4 (average particle size 4 μm) manufactured by Shin-Etsu Chemical Co., Ltd. Organic lubricant: Behenic acid amide BNT-22H manufactured by Nippon Fine Chemicals

[0118] (Raw materials used in the core layer) PP-2: Sumitomo Chemical Co., Ltd. Propylene-ethylene-butene random copolymer FL8115A (MFR 7.0 g / 10 min, melting point 148°C) PP-3: Propylene homopolymer FLX80E4 (MFR 7.5g / 10min, melting point 164℃) manufactured by Sumitomo Chemical Co., Ltd. LL-1: Braskem ethylene-hexene copolymer (plant-derived linear low-density polyethylene) SLH218 (MFR 2.3 g / min, density 916 kg / m3, melting point 126°C) LL-2: Sumitomo Chemical Co., Ltd. Ethylene-hexene copolymer (linear low-density polyethylene derived from fossil fuels) FV405 (MFR 4.0 g / min, density 923 kg / m3, melting point 118°C) LDPE-1: Braskem ethylene-hexene copolymer (plant-based low-density polyethylene) SLH818 (MFR8.1g / min, density 918kg / m3) Organic lubricant: Behenic acid amide BNT-22H manufactured by Nippon Fine Chemicals

[0119] (Materials used in the laminate layer) PP-2: Sumitomo Chemical Co., Ltd. Propylene-ethylene-butene random copolymer FL8115A (MFR 7.0 g / 10 min, melting point 148°C) PP-3: Propylene homopolymer FLX80E4 (MFR 7.5g / 10min, melting point 164℃) manufactured by Sumitomo Chemical Co., Ltd. LL-1: Braskem ethylene-hexene copolymer (plant-derived linear low-density polyethylene) SLH218 (MFR 2.3 g / min, density 916 kg / m3, melting point 126°C) LL-2: Sumitomo Chemical Co., Ltd. Ethylene-hexene copolymer (linear low-density polyethylene derived from fossil fuels) FV405 (MFR 4.0 g / min, density 923 kg / m3, melting point 118°C) LDPE-1: Braskem ethylene-hexene copolymer (plant-based low-density polyethylene) SLH818 (MFR8.1g / min, density 918kg / m3) These raw materials were mixed uniformly in the ratios shown in Table 2 to obtain a mixed raw material for producing an unstretched polyolefin film.

[0120] The mixed raw materials for the core layer were extruded in a three-stage single-screw extruder with a screw diameter of 90 mm, and the mixed raw materials for the seal layer and laminate layer were extruded in three-stage single-screw extruders with a screw diameter of 65 mm and 45 mm, respectively, in the order of seal layer / core layer / laminate layer. The preland was made into two stages with a width of 800 mm, and the step part was curved to make the flow of the molten resin uniform, and the mixture was extruded at an outlet temperature of 230° C. The thickness ratios of the laminate layer / intermediate layer / heat seal layer were 25% / 50% / 25%, respectively.

[0121] The molten resin sheet coming out of the die was cooled with a cooling roll at 35°C to obtain an unstretched polyolefin film with a thickness of 30 μm. When cooling with the cooling roll, both ends of the film on the cooling roll were fixed with an air nozzle, the entire width of the molten resin sheet was pressed against the cooling roll with an air knife, and at the same time, a vacuum chamber was operated to prevent air from being entrained between the molten resin sheet and the cooling roll. The air nozzles were installed in series with the film traveling direction at both ends. The die was surrounded by a sheet to prevent the molten resin sheet from being exposed to wind. In addition, the direction of the suction port of the vacuum chamber was aligned with the traveling direction of the extruded sheet.

[0122] The surface of the laminate layer of the film was subjected to corona treatment (power density 20 W min / m2). The film was formed at a speed of 20 m / min. The edges of the formed film were trimmed and the film was wound into a roll.

[0123] (CPP2~CPP 5, CPP7~CPP9, CPP13 ) In CPP1, the raw materials shown in Table 2 were used and unstretched polyolefin films having the thicknesses shown in Table 2 were obtained in the same manner. 。 C PP1~ CPP5, CPP7 to CPP9, CPP13The evaluation results of the film are shown in Table 2.

[0124] [Table 2A]

[0125] [Table 2B]

[0126] [Table 2C]

[0127] [Examples and Comparative Examples] <Preparation of heat-sealable laminated film> The biaxially stretched polyamide film and the unstretched polyolefin film obtained in Production Example 1 and Production Example 2 were coated with an ester adhesive obtained by mixing 33.6 parts by mass of a base agent (TM569, manufactured by Toyo Morton Co., Ltd.), 4.0 parts by mass of a curing agent (CAT10L, manufactured by Toyo Morton Co., Ltd.), and 62.4 parts by mass of ethyl acetate, so that the coating amount was 3.0 g / m2, and dry laminated. This was wound up and kept at 40°C, aged for 3 days, and then the heat-sealable laminated film was evaluated. Heat-sealable laminated films were produced and evaluated using the combinations of biaxially oriented polyamide films and unoriented polyolefin films shown in Table 3. The results are shown in Table 3.

[0128] [Table 3]

[0129] As shown in Table 3, the heat-sealable laminate films of the Examples had good heat seal strength, pinhole resistance due to bending, and resistance to bag breakage due to dropping, even when the biomass content was increased.

[0130] On the other hand, the heat-sealable laminate film using the biaxially oriented polyamide film of Comparative Examples 1 and 2 that did not contain a material to improve the pinhole resistance due to bending, and the biaxially oriented polyamide film of Comparative Example 3 that had too little polyamide 11 content, had poor pinhole resistance due to bending. In Comparative Example 4, since linear low-density polyethylene was not added to the core layer and the laminate layer, the bending pinhole resistance was poor. Comparative Example In 5 The heat seal strength was poor because of the large difference in the linear low density polyethylene content between the seal layer and the core layer. 。 ratio In Comparative Example 9, the core layer contained linear low-density polyethylene, but the laminate layer did not contain linear low-density polyethylene, and therefore the bending pinhole resistance was poor. 。 [Industrial Applicability]

[0131] The heat-sealable laminate film of the present invention is excellent in both impact resistance and pinhole resistance due to bending, and therefore can be suitably used as a packaging material for food packaging and the like.

Claims

1. A heat-sealable laminated film having at least a base layer and a sealant layer, The base layer is a biaxially oriented polyamide film, and the biaxially oriented polyamide film contains, as a polyamide resin, 70 to 99 mass% of polyamide 6 and 1 to 30 mass% of a polyamide at least a part of which is derived from biomass; The sealant layer is an unstretched polyolefin film, and the unstretched polyolefin film contains 70 to 95% by mass of a polypropylene-based resin and 5 to 30% by mass of a linear low-density polyethylene-based resin at least a part of which is derived from biomass; the sealant layer has a seal layer, a core layer and a laminate layer; The resin composition constituting the seal layer contains 94 to 100% by mass of a propylene-α-olefin random copolymer and 0 to 3% by mass of a linear low-density polyethylene, The resin composition constituting the core layer contains 25 to 97% by mass of a propylene-α-olefin random copolymer and 3 to 40% by mass of a linear low-density polyethylene, The resin composition constituting the laminate layer contains 25 to 70% by mass of a propylene-α-olefin random copolymer and 3 to 50% by mass of a linear low-density polyethylene, A heat-sealable laminate film, comprising, within the sealant layer, a laminate layer, a core layer, and a seal layer, which are arranged in this order from the surface in contact with the base layer.

2. 2. The heat-sealable laminate film according to claim 1, wherein the content of carbon-14 in the substrate layer is 1 to 30% based on the total carbon in the substrate layer.

3. 3. The heat-sealable laminate film according to claim 1, wherein the polyamide at least a part of which is derived from biomass in the base layer is at least one polyamide selected from the group consisting of polyamide 11, polyamide 410, polyamide 610, and polyamide 1010.

4. The heat-sealable laminate film according to any one of claims 1 to 3, wherein the content of carbon-14 in the sealant layer is 3 to 30% based on the total carbon in the sealant layer.

5. 5. The heat-sealable laminate film according to claim 1, wherein the carbon-14 content in the laminate film is 2 to 30% based on the total carbon in the laminate film.

6. A package using the heat-sealable laminate film according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Sheathing material for lithium ion battery

    JP2004296173A

  • Heat-sealable polyolefins

    JP2004501808A

  • Laminate equipped with polyolefin resin layer and packing product equipped with the same

    JP2018001612A

  • Easily opening sealant film

    JP2019151098A

  • Biaxially stretched polyamide film and laminate film

    WO2020170714A1